PENGARUH REMUNERASI, MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI LEMBAGA PEMASYARAKATAN KELAS IIB DOMPU - Lancur Ruktipriangga; I Nyoman Nugraha Ardana Putra; Siti Julaeha (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The aims of this study are to describe: (1) the effect of remuneration, motivation, and career development on the performance of the Class IIB Dompu Correctional Institution employees; and (2) the dominant influence on the performance of the Class IIB Dompu Correctional Institution employees. This research is a quantitative research that uses associative research type, and the population of this research is all 73 employees of the Class II-B Dompu Prison and used as the research sample. The research instrument used in data collection is a questionnaire. Then the data were analyzed using multiple linear regression statistics. The results of the study are that: (1) Remuneration has a positive and significant effect on the performance of the Class IIb Dompu Prison employees. With income that is in accordance with the needs of the family, it will cause employees to be more enthusiastic in working which in turn can improve work ethic; (2) Motivation has a positive and significant influence on the performance of Class IIb Dompu Prison employees. Motivation is an encouragement in employees in carrying out tasks that will give positive results to the quality and quantity of their work. The higher a person's work motivation, the higher the employee's work productivity. (3) Career development has a significant and positive effect on employee performance. This means that in improving employee performance, career development planning and management can be carried out; (4) Remuneration is the most dominant variable affecting the performance of Class IIb Dompu Lapas employees.